2008
DOI: 10.1002/qua.21646
|View full text |Cite
|
Sign up to set email alerts
|

Quantum mechanical model for Maya Blue

Abstract: This work is about Maya Blue (MB), a pigment developed byMesoamerican civilizations between the 5th and 16th centuries from an aluminosilicate mineral (palygorskite) and an organic dye (indigo). Two different supramolecular quantum-mechanical models afford explanations for the unusual stability of MB based on the oxidation of the indigo molecule during the heating process and its interaction with palygorskite. A model considering indigo derivatives attached to several aluminates shows the principal features of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 38 publications
2
29
1
Order By: Relevance
“…It has been proposed that indigo could mostly bond to AIH rather than Mg 2 + [26]. This interaction is supposed to play a capital role in the indigo -clay association [20,21]. However, the associ ation clay -indigo via the octahedral Ae+ seems improbable (if not completely inexistent), because there is no evidence that this cation can occupy the external octahedral positions at the tunnel edges [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been proposed that indigo could mostly bond to AIH rather than Mg 2 + [26]. This interaction is supposed to play a capital role in the indigo -clay association [20,21]. However, the associ ation clay -indigo via the octahedral Ae+ seems improbable (if not completely inexistent), because there is no evidence that this cation can occupy the external octahedral positions at the tunnel edges [12].…”
Section: Discussionmentioning
confidence: 99%
“…A second possible structural approach proposed by Kleber et al [17] would allow indigo to penetrate (partially or deeper) into the clay tunnels. It can be found literature supporting Van Olphen [18][19][20][21][22] and Kleber [13,[23][24][25][26] models. More recently, Hubbard et al [6] suggested the covering of the opening of nano-tmmels by the indigo molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between PAL and indigo is the origin of the high stability of Maya Blue, but the real nature of the interaction remains controversial. The most widely acknowledged interactions encompass hydrogen bonding between (i) carbonyl and amine groups of indigo and peripheral silanol groups of PAL [11]; (ii) carbonyl and amine groups of indigo and structural silanol groups of PAL [12,13]; and (iii) carbonyl group and coordinated water as well as the interaction between indigo molecule and the Mg 2+ and Al 3+ ions inside the octahedral PAL [13][14][15]. However, the definite position of indigo molecules in PAL is still in dispute.…”
Section: Introductionmentioning
confidence: 96%
“…The indigo-palygorskite association has been attributed to the formation of hydrogen bonds between C@O of indigo molecules and structural water molecules [9,11,15,16], with minor contribution of the hydrogen bonding between structural water molecules and N-H units of indigo [15]. Formation of hydrogen bonds between the carbonyl and amino groups of indigo with edge silanol units of the clay [14], bonding to Mg 2+ -coordinated water molecules in the inner surface of the tunnels or the direct bonding to the Mg 2+ and/or exposed Al 3+ ions at the edge of palygorskite tunnels [16][17][18][19][20] have been also proposed. The influence of Van der Waals interactions [10] and the possibility of head-to-tail interaction of indigo molecules in the channels of the clay [22] have also been commented.…”
Section: Introductionmentioning
confidence: 98%